1998
DOI: 10.1159/000016497
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fluorosis and Nutritional Status of 6– to 11–Year–Old Children Living in Rural Areas of Paraíba, Brazil

Abstract: The aim of this study was to investigate the relationship between nutritional status and dental fluorosis in areas with fluoride in the drinking water in Paraíba, Brazil. Rural villages of comparable low socio–economic status and stable water fluoride levels were selected. Lifelong residents (6–11 years old, n = 650) were examined for nutritional status (height–for–age index; WHO methods) and dental fluorosis of central incisors and first molars (TF index). The sample was divided into three groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…There was no increase in enamel defects in children regardless of whether they lived in fluoridated areas or not 12,13 . In the state of Paraíba, north‐eastern Brazil, some studies indicated the presence of naturally fluoridated waters and a considerable prevalence of dental fluorosis 15,16 . There are, however, no studies to date addressing the relationship between residual fluoride levels in drinking water in Brazil and the occurrence of MIH.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…There was no increase in enamel defects in children regardless of whether they lived in fluoridated areas or not 12,13 . In the state of Paraíba, north‐eastern Brazil, some studies indicated the presence of naturally fluoridated waters and a considerable prevalence of dental fluorosis 15,16 . There are, however, no studies to date addressing the relationship between residual fluoride levels in drinking water in Brazil and the occurrence of MIH.…”
Section: Introductionmentioning
confidence: 90%
“…Dental fluorosis is historically endemic in these municipalities. This is a semi‐desert region with high annual mean maximum temperatures and few sources of water 15,16 . Hence, it must be pointed out that the water source at home is the same as in each rural school.…”
Section: Methodsmentioning
confidence: 99%
“…The concomitant decline in the prevalence of dental caries and increase in the prevalence of dental fluorosis has been observed in both optimally fluoridated and non-fluoridated areas in many countries, as well in Brazil (Correia Sampaio et al 1999, Fomon et al 2000, Pereira et al 2000, Levy et al 2001. This increases the responsibility of health professionals in terms of correctly educating parents with respect to the balanced fluoride intake, especially at the age of risk to dental fluorosis development.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information in the literature on this association, and the data that are available are inconsistent. In Brazilian schoolchildren from Paraíba, undernutrition was not associated with dental fluorosis (Correia-Sampaio et al, 1999). However, the fluoride dosages that the Brazilian children in the study group were exposed to were likely lower than those to which the Mexican schoolchildren in this study group were exposed because both salt (200 mg F − /kg salt) and water had fluoride (NOM, 1993).Mexico's National Salt Fluoridation Program was legislated in 1993; therefore, it is likely that the schoolchildren in the current study were exposed to fluoridated salt from birth (Martínez-Salgado et al, 1993).…”
Section: Discussionmentioning
confidence: 86%